Peran Dakwah Islam Dalam Upaya Mengatasi Penyalahgunaan Narkoba - Muqoddam Cholil; Nu'man Hujatullah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
The purpose of this study was to determine the role of Islamic preaching to solving the drug problem in RW 01 and RW 06 Rawa Badak Selatan, North Jakarta. The research methodology used descriptive qualitative approach. The results showed that proselytism is divided into 2 (two): First. Proselytism as a preventive factor. Second, the call of religion as a curative factor that is by always delivering good news or basyran and news nadhiran threat or end later in the day (of doom). Religion takes as one factor to rehabilitate mentally and bad characteristics become aware and conscious of his guilt.